Cavitation Effects on the Stability of a Submerged Journal Bearing - Jerzy T. Sawicki; T. V. V. L. N. Rao (International Journal of Rotating Machinery)
A computational procedure for the mechanism of shear between the liquid sublayer and air cavity in the cavitation zone of a submerged journal bearing is presented here. Using the mass conservation principle, Elrod's universal equation is modified to take into consideration the shear of the air cavity in the cavitation region. Results of steady state and transient response for the submerged journal bearing using the present approach are compared with the universal equation based on the striated flow in the cavitation region. At steady state, the angular extent of cavitation region predicted by the present approach is higher than that predicted by Elrod's model and the limit cycle journal transient response using the present approach predicts higher eccentricity ratios.